Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27807
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Twin-Entry Radial Inflow Gas Turbine With Unsymmetrical Volute Under Full and Partial Admission Conditions

Abstract: In this paper the performance characteristics of turbocharger twin-entry radial inflow gas turbine with unsymmetrical volute and rotor tip diameter of 73.6 mm in steady state and under full and partial admission conditions are investigated. The employed method is based on one dimensional performance prediction which is developed for partial admission conditions. Furthermore this method is developed for unsymmetrical volute of the turbine considering flow specifications. Experimental investigation of the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Despite these improvements, some new phenomena arise in the space after the union of both volutes that must be taken into account. Numerous authors have experimentally characterised twin-entry turbines focusing on the blade loading loss in the rotor as Aghaali and Hajilouy-Benisi, 14 the acoustic response as Serrano et al, 15 the swallowing capacity as Romagnoli et al, 16 the effect of integrating a balance valve as Jin et al 17 or the unequal admission conditions as Brinkert et al 18 Other authors have carried out a loss analysis of twin-entry turbines using also CFD simulations. Xue et al 19 simulated a twin-entry mixed flow nozzled turbine and they calculated the losses separately for the volute, the nozzle and the rotor using loss coefficients based on the stagnation pressure for each part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these improvements, some new phenomena arise in the space after the union of both volutes that must be taken into account. Numerous authors have experimentally characterised twin-entry turbines focusing on the blade loading loss in the rotor as Aghaali and Hajilouy-Benisi, 14 the acoustic response as Serrano et al, 15 the swallowing capacity as Romagnoli et al, 16 the effect of integrating a balance valve as Jin et al 17 or the unequal admission conditions as Brinkert et al 18 Other authors have carried out a loss analysis of twin-entry turbines using also CFD simulations. Xue et al 19 simulated a twin-entry mixed flow nozzled turbine and they calculated the losses separately for the volute, the nozzle and the rotor using loss coefficients based on the stagnation pressure for each part.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements, some new phenomena arise in the space after the union of both volutes that must be taken into account. Numerous authors have experimentally characterised twin-entry turbines focusing on the blade loading loss in the rotor as Aghaali and Hajilouy-Benisi, 14 the acoustic response as Serrano et al, 15 the swallowing capacity as Romagnoli et al, 16 the effect of integrating a balance valve as Jin et al 17 or the unequal admission conditions as Brinkert et al 18…”
Section: Introductionmentioning
confidence: 99%
“…However, twin-entry turbines present new issues in the interspace between both volute outlets and the rotor inlet. Aghaali and Hajilouy-Benisi 9 and Brinkert et al 10 carried out experimental tests for analysing the effect of the different admission conditions. These studies demonstrated the flow admission conditions have a strong effect on the flow behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Recently, Aghaali et al [5] were interested in performance characteristics of radial turbine of a double input turbocompressor with an asymmetric volute at stationary state taking into consideration the complete and partial admission conditions. Sloteman et al [6] had developed a design methodology based on the combination of one-dimensional analysis method of performance and an inverse method for blade generation.…”
Section: Introductionmentioning
confidence: 99%